A journey - Blair, Tony, 1953- (London : Hutchinson, 2010)
Tony Blair's own account of his political life, his rise to power, his life on the world stage, and the clashes, controversies and triumphs of one of the most successful political careers of modern times.
Includes index.
Keywords: Blair, Tony, -- 1953-; Labour Party (Great Britain) -- Biography; Ex-prime ministers -- United Kingdom -- Biography; Prime ministers -- United Kingdom -- Biography; Politicians -- United Kingdom -- Biography; United Kingdom -- Politics and government -- 1997-2007.; United Kingdom -- Foreign relations -- 1997-